Bifidobacterium longum suppresses colorectal cancer through the modulation of intestinal microbes and immune function - Shang, Fangjian; Jiang, Xia; Wang, Haobo; Guo, Shang; Kang, Shuo; Xu, Bin; Wang, Xin; Chen, Shihao; Li, Ning; Liu, Bo; Zhao, Zengren (Frontiers in Microbiology, 2024)
Colorectal cancer (CRC), one of the most common malignancies in the world, urgently requires more treatment strategies. Although there has been much research on probiotics, limited research has been done in treating cancer. The purpose of this study was to investigate the role of Bifidobacterium longum (B. longum) in the prevention and treatment of CRC. Through Cell Counting Kit-8 and Colony Formation Assays, 8 h and a B. longum count of 1×10 8 CFU/ml were chosen as the best cocultivation conditions with CRC cells. The role of B. longum in inhibiting the progression of CRC cells was verified by a series of functional and immunofluorescence assays. For instance, in vivo assays have verified that B. longum could alleviate CRC progression. In addition, according to the results of in vivo assays and clinical statistical analysis, B. longum could reduce diarrhea symptoms. Mechanistically, by 16S and RNA sequencing, it was found that B. longum could affect the development of CRC by regulating the composition of gut microbes and enhancing immune function. The B. longum might inhibit the occurrence and development of CRC and relieve diarrhea symptoms by regulating intestinal microbes and immune function.